CANCER = DEATH Treatment of Cancer The Chinese Way - Xie, Wenwei (New World Press, 1997)
The book consists of 100 cases of successful treatment of cancer using Chinese herbal medicine. The diagnoses made in these cases are accurate, while the majority has involved cellular pathological diagnosis. Most of the patients in the listed cases have been treated mainly by Chinese medicine. These patients have been cured or at least their survival period has been greatly prolonged. In each case, there is medical history of the patient, and the author has made an analysis and evaluation while providing remarks on the herbs and formulae administered. Also, in writing this book, the author has no intention to reject treatment of cancer by using modern medicine, but rather to combine traditional Chinese medicine with Western medicine. At the end of the book there is a list of 160 effective anticancer formulae for reference.